Factors Associated with Dengue Hemorrhagic Fever in the Lepo-Lepo Community Health Center Area - Nur Alya; Erwin Azizi Jayadipraja; Fitri Yanti (Miracle Journal of Public Health, 2025)
Dengue Hemorrhagic Fever is one of the health problems in Indonesia that tends to increase in the number of patients and spread more widely and can cause extraordinary events (KLB). The prevalence of DHF in Kendari City in 2024 is 0.474% or 474/100,000 population, while the national figure is 0.03%. The purpose of this study was to determine the factors associated with DHF cases in the community within the working area of the Lepo-Lepo Community Health Center through an epidemiological study approach. This was a quantitative study with a cross-sectional design. The population consisted of 7,134 households, with a sample size of 99 respondents. The sampling technique used was proportional random sampling. The analysis method used the chi-square test. The results showed that DHF was significantly related to PSN knowledge (0.000<0.05), 3M Plus behavior (0.000<0.05), resting places (0.029<0.05), and indoor air humidity (0.003<0.05). The conclusion is that there is a relationship between PSN knowledge, 3M Plus behavior, resting place, and indoor air humidity. This study suggests that efforts to prevent DHF in the Lepo-Lepo Community Health Center working area should focus on intensively improving education and socialization regarding mosquito breeding site eradication (PSN) and 3M Plus behavior to the community. In addition, environmental control, such as managing mosquito resting places and regulating indoor air humidity, should be a priority to reduce the habitat of Aedes aegypti mosquitoes.